Heavy metals distribution in mangrove leaves in various sudanese coastal zones at the red sea - Mohammad Khalil, Rabha Khalil; Solangi, Kashif Ali; Alhassan, Abdullahi Bala; Khan, Waseem Razzaq; Aljahdali, Mohammed Othman (Global NEST, 2024)
Mangrove ecosystem contamination, especially in the Red Sea region, has caused major concerns on a worldwide scale. The heavy metal accumulation typical of a mangrove species, Avicenna marina L.,(A. marina) leaves and soluble salts in sediments have not been studied on the Red Sea coast of Sudan. The present study investigates the two nutrients calcium (Ca) and iron (Fe) and heavy metals such as barium (Ba), titanium (Ti), and strontium (Sr) in the mangrove species A. marina in the leaves of six different locations in the Red Sea coastal area, as follows: (Hamasyat (HM) Keligo (KG), and Enkfel (EK) of the Gulf of Dunnabeb, and three sites were selected in the south of the Sudanese coast as follows: (Amarat Island (AM), Ibn Abbas Island (BN), and Ras Kassar (RK). The results demonstrate that the maximum calcium (Ca)and iron (Fe) concentrations in mangrove leaves were 35.9 mg/kg and 4.10 mg/kg recorded at RK and AM, respectively, in the south region of the Red Sea. The heavy metal concentrations (mg/kg) vary between different locations. The higher concentration of heavy metals in mangrove leaves increased as Ba was 1.1 mg/kg in the EG north region. While Ti (0.5 mg/kg) and Sr (2.80 mg/kg) higher concentrations were recorded in AM and EK, respectively, in the south area than in the other experimental sites. Heavy metals and soluble salts in sediments are continuously monitored in mangrove habitats to ensure they keep within allowed limits. These results could be useful as a database for prospective ecological research, preservation efforts, and long-term sustainable management of the Sudanese mangrove ecosystems throughout the Red Sea coastal.